“The vice of distant knowledge”: Licensing and the geography of jurisdiction on the Scottish wartime Home Front - Beckingham, David (Elsevier, 2017)
This article considers how licensing law conceives and practices jurisdiction. It examines the limits of attempts to define and exploit jurisdiction in the regulation of social problems connected to alcohol. Using the case study of a prohibition on the sale of spirits in the Scottish town of Motherwell during the First World War, it analyses how ‘vertical’ legal appeals through higher courts intersected with everyday ‘horizontal’ challenges to the jurisdiction of the local licensing magistrates as the ban pushed drinkers and the problems of drunkenness onto neighbouring authorities. Those higher court challenges importantly confirmed the localness of licensing, but they could not guarantee the effectiveness of the magistrates’ policy. By showing the potentially disruptive daily habits of ordinary citizens and urban infrastructure, the article promotes a social and material legal geography of licensing. In conclusion, it calls for a critical examination of the ‘local’ in local government, and the political geographies that result from appeals to space and scale in the division of governance functions.